2013
DOI: 10.1128/jvi.02655-12
|View full text |Cite
|
Sign up to set email alerts
|

Human MicroRNA hsa-miR-296-5p Suppresses Enterovirus 71 Replication by Targeting the Viral Genome

Abstract: Enterovirus 71 (EV71) has emerged as a major cause of neurological disease following the near eradication of poliovirus. Accumulating evidence suggests that mammalian microRNAs (miRNAs), a class of noncoding RNAs of 18 to 23 nucleotides (nt) with important regulatory roles in many cellular processes, participate in host antiviral defenses. However, the roles of miRNAs in EV71 infection and pathogenesis are still unclear. Here, hsa-miR-296-5p expression was significantly increased in EV71-infected human cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
159
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 167 publications
(162 citation statements)
references
References 58 publications
3
159
0
Order By: Relevance
“…On the other hand, miR-196, miR-351, miR-431, and miR-448 inhibit HCV replication in Huh7 cells by interacting with the HCV genome (36). Recently, miR-296-5p was shown to inhibit enterovirus 71 replication by binding to the VP-1 gene (37). Our study demonstrated that the introduction of miR-181c into HCVinfected hepatocytes or cells harboring the HCV genome-length replicon inhibits viral genome replication.…”
Section: Discussionmentioning
confidence: 70%
“…On the other hand, miR-196, miR-351, miR-431, and miR-448 inhibit HCV replication in Huh7 cells by interacting with the HCV genome (36). Recently, miR-296-5p was shown to inhibit enterovirus 71 replication by binding to the VP-1 gene (37). Our study demonstrated that the introduction of miR-181c into HCVinfected hepatocytes or cells harboring the HCV genome-length replicon inhibits viral genome replication.…”
Section: Discussionmentioning
confidence: 70%
“…Recombinant EV71 mutants harboring 3D mutations were constructed by overlapping extension PCR using the infectious clone as a template at the indicated sites. Verification of the mutants was performed by RNA extraction, reverse transcription, and PCR (39).…”
Section: Cellmentioning
confidence: 99%
“…The EV71 infectious clone and its mutant recombinant RNAs were in vitro transcribed with a RiboMax large-scale RNA production system T7 kit (Promega) (43). The RNAs were transfected into Vero cells to rescue EV71 wild-type (WT) and mutant viruses, and these viral strains were amplified in RD cells (39).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…miR-122, a liver-specific miRNA, interacts with the 5= UTR of the genome of the hepatitis C virus (HCV) and increases viral replication (13). miR-296-5p and miR-141 are upregulated to modulate EV71 replication by targeting the viral genome and host eIF4E, respectively (14,15).…”
mentioning
confidence: 99%